Low-dimensional hybrid perovskites as high performance anodes for alkali-ion batteries - Tathavadekar, Mukta; Krishnamurthy, Shrreya; Banerjee, Aparna; Nagane, Satyawan; Gawli, Yogesh; Suryawanshi, Anil; Bhat, Suresh; Puthusseri, Dhanya; Mohite, Aditya D.; Ogale, Satishchandra (Journal of Materials Chemistry A, 2017)
State-of-the-art Li (or Na) ion batteries work by insertion/extraction of the alkali metal ions into a porous electrode material, where the overall capacity is strongly dependent on the accessibility of the host material interior to the ions. On the other hand, the performance stability depends on various factors governed by the specific constitution of the electrode. Here we show that molecularly engineered low-dimensional hybrid perovskites can work as excellent anode materials for alkali-ion batteries. We measure a high reversible capacity of 646 mA h g(-1) at 100 mA g(-1) with good stability tested up to 250 cycles for the benzidine mediated lead iodide based 1D system. An ex situ analysis of the electrodes reveals that the storage primarily occurs via the Li-x(or Na-x)Pb alloying/de-alloying process. We anticipate that these results open a new direction for the use of low-dimensional hybrid perovskites for energy storage applications.
Keywords: Generation; Inorganic-Organic Hybrid; Lead Iodide; lithiation-intramolecular electrophilic reaction; Na-Air Battery; Negative Electrodes; Organometal Halide perovskites; PB; Sequential Deposition; Solar-cells